Population Abundance of Potentially Pathogenic Organisms in Intestinal Microbiome of Jungle Crow (Corvus macrorhynchos) Shown with 16S rRNA Gene-Based Microbial Community Analysis. (24th August 2013) - Maeda, Isamu; Siddiki, Mohammad Shohel Rana; Nozawa-Takeda, Tsutomu; Tsukahara, Naoki; Tani, Yuri; Naito, Taki; Sugita, Shoei
Abstract : Jungle Crows ( Corvus macrorhynchos ) prefer human habitats because of their versatility in feeding accompanied with human food consumption. Therefore, it is important from a public health viewpoint to characterize their intestinal microbiota. However, no studies have been involved in molecular characterization of the microbiota based on huge and reliable number of data acquisition. In this study, 16S rRNA gene-based microbial community analysis coupled with the next-generation DNA sequencing techniques was applied to the taxonomic classification of intestinal microbiome for three jungle crows. Clustering of the reads into 130 operational taxonomic units showed that at least 70% of analyzed sequences for each crow were highly homologous to Eimeria sp., which belongs to the protozoan phylum Apicomplexa . The microbiotas of three crows also contained potentially pathogenic bacteria with significant percentages, such as the genera Campylobacter and Brachyspira . Thus, the profiling of a large number of 16S rRNA gene sequences in crow intestinal microbiomes revealed the high-frequency existence or vestige of potentially pathogenic microorganisms.